Light-activated oxygen self-supplied starving therapy in near-infrared (NIR) window and adjuvant hyperthermia-induced tumor ablation with an augmented sensitivity. (March 2020) - Ren, Junjie; Zhang, Lei; Zhang, Jiayi; Zhang, Wei; Cao, Yang; Xu, Zhigang; Cui, Hongjuan; Kang, Yuejun; Xue, Peng
Abstract: Glucose oxidase (GOx)-mediated starvation circumvents the energy supply for tumor growth, which has been proved as a potent tumor treatment modality. However, tumor hypoxia negatively affects the efficacy of oxygen-involved glucose decomposition reaction. Moreover, curative effect via glucose depletion is not usually satisfactory enough and adjuvant remedies are always required for a promoted tumor ablation. Herein, a multifunctional nanoreactor based on hollow Bi2 Se3 nanoparticles was developed by loading oxygenated perfluorocarbon (PFC) and surface modification with GOx, which was exploited for an enhanced tumor starvation and highly sensitive photothermal therapy (PTT). GOx-mediated tumor starvation could impede the adenosine triphosphate (ATP) generation and further downregulate the expression of heat shock protein (HSP) to decrease the thermoresistance of cells. Afterwards, near infrared (NIR) laser irradiation was performed not only to trigger sensitized PTT but also to initiate the release of encapsulated oxygen to relieve local hypoxia. Then, such GOx-mediated tumor starvation would be further amplified, accompanying with secondary enhanced suppression of HSP. Both in vitro and in vivo investigations demonstrated that such nanoreactor can realize a fascinating therapeutic outcome with minimal adverse effects in virtue of the improved synergistic starvation therapy and PTT. Taken together, the proposed treatment paradigm may inspire the future development of more intelligent nanoplatforms toward high efficient cancer therapy.